Restructuring and merger waves - Rodrigues, Vasco (2016)
Although merger waves are one of the most important market structures shaping forces, they have been the object of little theoretical investigation in industrial economics. This paper explains how the occurrence of industry merger waves is determined by the interplay between the synergy opportunities offered by mergers and the possibility to free-ride other firms ' mergers market power effects. This explanation arises in the context of a two-stage model in which mergers are endogenously determined before firms compete in the product 's market. The endogenous market structure can either be excessively or insufficiently concentrated from a total surplus perspective.